Genetic and Pharmacological Inhibition of Retinoic Acid Receptor γ Function Promotes Endochondral Bone Formation - Uchibe, Kenta (J Orthop Res, 2016)
The nuclear retinoic acid receptors (RARs) play key roles in skeletal development and endochondral ossification. Previously we showed that RARγ regulates chondrogenesis and that pharmacological activation of RARγ blocked heterotopic ossification (HO), pathology in which endochondral bone forms in soft tissues. Thus, we reasoned that pharmacological inhibition of RARγ should enhance endochondral ossification, leading to a potential therapeutic strategy for bone deficiencies. We created surgical bone defects in wild type and RARγ-null mice and monitored bone healing. Fibrous, cartilaginous and osseous tissues formed in both groups by day 7, but more cartilaginous tissue formed in mutants within and around the defects compared to controls. Next, we implanted a mixture of Matrigel and rhBMP2 subdermally to induce ectopic endochondral ossification. Administration of RARγ antagonists significantly stimulated ectopic bone formation in wild type but not in RARγ-null mice. The antagonist-induced increases in bone formation were preceded by increases in cartilage formation and were accompanied by higher levels of phosphorylated Smad1/5/8 (pSmad1/5/8) compared to vehicle-treated control. Higher pSmad1/5/8 levels were also observed in cartilaginous tissues forming in healing bone defects in RARγ-null mice, and increases in pSmad1/5/8 levels and Id1-luc activity were observed in RARγ antagonist-treated chondrogenic cells in culture. Our data show that genetic or pharmacological interference with RARγ stimulates endochondral bone formation and does so at least in part by stimulating canonical BMP signaling. This pharmacologic strategy could represent a new tool to enhance endochondral bone formation in the setting of various orthopaedic surgical interventions and other skeletal deficiencies.